Inducing Frictional Force to Enhance the Transient Response in Beams - Mina, Hamed Khanger; Al-Ashtrai, Waleed K. (Al-Nahrain Journal for Engineering Sciences, 2019)
This paper studies the effect of contact areas on the transient response of mechanical structures. Precisely, it investigates replacing the ordinary beam of a structure by two beams of half the thickness, which are joined by bolts. The response of these beams is controlled by adjusting the tightening of the connecting bolts and hence changing the magnitude of the induced frictional force between the two beams which affect the beams damping capacity._x000D_A cantilever of two beams joined together by bolts has been investigated numerically and experimentally. The numerical analysis was performed using ANSYS-Workbench version 17.2. A good agreement between the numerical and experimental results has been obtained. In general, results showed that the two beams vibrate independently when the bolts were loosed and the structure stiffness is about 20 N/m and the damping ratio is about 0.008. With increasing the bolts tightening, the stiffness and the damping ratio of the structure were also increased till they reach their maximum values when the tightening force equals to 8330 N, where the structure now has stiffness equals to 88 N/m and the damping ratio is about 0.062. Beyond this force value, increasing the bolts tightening has no effect on stiffness of the structure while the damping ratio is decreased until it returned to 0.008 when the bolts tightening becomes immense and the beams behave as one beam of double thickness.